Tail dependence between gold and sectorial stocks in China: Insights for portfolio diversification - Beckmann, Joscha (Trường Đại học Kinh tế, 2020)
This article analyzes dynamics of relationship between gold quoted on the Shanghai Gold Exchange and Chinese sectorial stocks from 2009 to 2015. Using different copulas, our results show that there is weak symmetric tail dependence between gold and sectorial stocks. Based on the efficient frontier, optimal weight, hedge ratio and hedging effectiveness, we find that adding gold to Chinese stock portfolios can help to reduce their risk. Gold appears to be the most efficient with stocks of the Energy, Information, Telecommunication and Materials sectors and the less efficient with the Utilities sector. As a robustness check, gold is compared to oil and the results show that gold is also more efficient than oil in the diversification of Chinese stock portfolios